2005
DOI: 10.1002/jssc.200500167
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of etched electrochemical detection for electrophoresis in micron inner diameter capillaries

Abstract: SUMMARYAn enhanced etched electrochemical detection technique has been developed for capillary electrophoresis in micron inner diameter capillaries. The design improvements allow for better alignment between the capillary bore and the electrode. This new method involves utilizing a carbon fiber microelectrode and etching both the carbon fiber and the detection end of a micrometer-sized inner diameter capillary to limit dead volume and analyte diffusion at the amperometric electrochemical detector. To understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
(32 reference statements)
0
10
0
1
Order By: Relevance
“…This resulted in an etch with a frustum geometry measuring approximately 40 µm wide at the base, which serves to both ease placement of the electrode at the capillary outlet, as well as to decouple the applied separation voltage from the electrochemical cell (43). …”
Section: Methodsmentioning
confidence: 99%
“…This resulted in an etch with a frustum geometry measuring approximately 40 µm wide at the base, which serves to both ease placement of the electrode at the capillary outlet, as well as to decouple the applied separation voltage from the electrochemical cell (43). …”
Section: Methodsmentioning
confidence: 99%
“…The researchers have taken measures, such as modifying the electrodes [32,33] or reducing the size of the microchannel and electrode [34,35] to improve the sensitivity of the CE-ECD system. Ewing and coworkers [31,[34][35][36][37] investigated the influence of the size of the column and the working electrode on the sensitivity of amperometric detection, and the results demonstrated that reducing the size of the column and the working electrode to a certain degree actually enhanced the sensitivity.…”
Section: Introductionmentioning
confidence: 96%
“…A CE system with end-column amperometric detection was built in-house and used as previously described 30. Modifications were made to the system to integrate hydrodynamic flow of lysis buffer into the detection zone.…”
Section: Methodsmentioning
confidence: 99%